The Foundations of Textual Coherence in the Ancient Linguistic Heritage (Arabic grammar as an example) - مرزوق , فاتح (Milev Journal of Research and Studies, 2023)
Textual coherence is one of the main pillars for building a text. Rather, it is the building block on which the overall coherence is based; at that time, tight coherence and consistency occurs between the various linguistic structures; Grammar is based on linguistic relationships that are stable in the essence of synthetic patterns. Because the purpose of this coherence is to highlight the communicative interaction between the two elements of communication; that is the speaker and the listener. It is appropriate to point out that the linguistic structures in the modern linguistic lesson are similar to the old grammatical lesson. in building the foundations of harmony and cohesion; Beginning with Sibawayh to the era of Abd al-Qaher al-Jurjani, however, the studies developed and extended to bring about a shift in the linguistic study to move from the sentence to the broader one, which is the text. From this point of view, we intend to answer the following problem: What are the scientific bases for textual coherence in the ancient grammar lesson? What are the rules established by linguists to link textual coherence and linguistic communication?